Use of Strategic Tools in Farm Management: Evidences From The Brazilian Countryside (Management and Connections Journal, 2020)
This study aimed to identify the characteristics associated with the use of strategic tools in the context of rural properties. For this, a survey was carried out, with a sample of 181 farmers from the Dourados microregion, Mato Grosso do Sul state, Brazil. The association of variables was tested using the  statistics,  coefficient and Cramer  coefficient. The results showed that the use of strategic tools is associated with the level of knowledge about strategic management, educational level, farm size, use of control systems, separation of farm spending from family spending and level of knowledge about cost management. It was verified that there were advances in terms of strategic management practices adoption, but informal or undeveloped management predominates in the farms surveyed